2016
DOI: 10.1111/wrr.12456
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of cryopreserved umbilical cord as an adjunctive therapy to promote the healing of chronic, complex foot ulcers with underlying osteomyelitis

Abstract: Complex lower extremity ulcers with exposed bone, tendon, muscle, and/or joint capsule as well as multiple comorbidities including diabetes, ischemia, and underlying osteomyelitis are difficult to heal and associated with high morbidity and mortality and high rates of amputation. A retrospective review was performed to assess healing of 31 patients presenting with 33 complex foot ulcers with a confirmed histopathological diagnosis of osteomyelitis treated by the same surgeon at a single wound care center by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…In addition, Theraskin is not indicated for ulcers with severe infection including osteomyelitis. Aside from the present study, successful use of cUC in treating complex DFUs with osteomyelitis has been reported in two retrospective studies . In the first study, 26 of 33 (79%) wounds achieved complete wound closure in 16 ± 9.3 (range: 4–44) weeks with 1.2 ± 0.4 cUC applications.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…In addition, Theraskin is not indicated for ulcers with severe infection including osteomyelitis. Aside from the present study, successful use of cUC in treating complex DFUs with osteomyelitis has been reported in two retrospective studies . In the first study, 26 of 33 (79%) wounds achieved complete wound closure in 16 ± 9.3 (range: 4–44) weeks with 1.2 ± 0.4 cUC applications.…”
Section: Discussionsupporting
confidence: 53%
“…In comparison with acellular dermal matrix where there was an equal amount of cellular ingrowth, there was decreased acute inflammation and more organized cellular ingrowth of epidermal and meningeal cells in the human cUC . Preliminary studies using the commercially available UC product NEOX™ CORD 1K (Amniox Medical, Inc., Miami, FL) further suggest cUC is safe and useful in promoting healing of complex foot ulcers with osteomyelitis, with healing rates reported from 79 to 100% when combined with negative pressure therapy . TTAX01, an investigation biologic form of the cUC made under Good Manufacturing Practices with additional validations and potency measurements, also contains these potentially beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small retrospective studies show that it may be helpful in wound healing, but RCTs are warranted to evaluate its true efficacy. 82,83 Energy-based therapies Energy-based therapies employ technology to externally stimulate growth in wounds. Modalities currently being studied include electrical stimulation, shockwave therapy, electromagnetic therapy, laser therapy, and phototherapy.…”
Section: Skin Grafts and Bioengineered Skinmentioning
confidence: 99%
“…A third retrospective study examined the efficacy and safety of NEOX cryopreserved umbilical cord in treatment of complex lower extremity ulcers involving exposed bone, muscle, tendon, or joint capsule within the background of underlying osteomyelitis (22). Seventy-eight percent of these complex wounds achieved complete closure, with a median time-to-heal of 16 weeks using an average of 1.24 applications of NEOX Wound Allograft ( Table 1).…”
Section: Amniotic and Placental Membranesmentioning
confidence: 99%